2014
DOI: 10.1371/journal.pone.0090230
|View full text |Cite
|
Sign up to set email alerts
|

Polar Localization of PhoN2, a Periplasmic Virulence-Associated Factor of Shigella flexneri, Is Required for Proper IcsA Exposition at the Old Bacterial Pole

Abstract: Proper protein localization is critical for bacterial virulence. PhoN2 is a virulence-associated ATP-diphosphohydrolase (apyrase) involved in IcsA-mediated actin-based motility of S. flexneri. Herein, by analyzing a ΔphoN2 mutant of the S. flexneri strain M90T and by generating phoN2::HA fusions, we show that PhoN2, is a periplasmic protein that strictly localizes at the bacterial poles, with a strong preference for the old pole, the pole where IcsA is exposed, and that it is required for proper IcsA expositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 63 publications
2
34
0
Order By: Relevance
“…The IgA response to E. coli is dependent on Tfh cells in PPs (Lécuyer et al., 2014) and is significantly more effective in P2rx7 −/− mice (Proietti et al., 2014), suggesting that P2X7 activity can affect the T cell-dependent IgA response. We used a recombinant E. coli K-12 strain carrying the pHND10 plasmid, which encodes phoN2 ::HA fusion of Shigella flexneri , a periplasmic ATP-diphosphohydrolase (apyrase) (Santapaola et al., 2006, Scribano et al., 2014). Extracellular ATP released concomitantly with E. coli growth (Hironaka et al., 2013) was undetectable in cultures of these transformants, indicating that apyrase efficiently abrogated ATP secretion (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The IgA response to E. coli is dependent on Tfh cells in PPs (Lécuyer et al., 2014) and is significantly more effective in P2rx7 −/− mice (Proietti et al., 2014), suggesting that P2X7 activity can affect the T cell-dependent IgA response. We used a recombinant E. coli K-12 strain carrying the pHND10 plasmid, which encodes phoN2 ::HA fusion of Shigella flexneri , a periplasmic ATP-diphosphohydrolase (apyrase) (Santapaola et al., 2006, Scribano et al., 2014). Extracellular ATP released concomitantly with E. coli growth (Hironaka et al., 2013) was undetectable in cultures of these transformants, indicating that apyrase efficiently abrogated ATP secretion (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The best-studied case is that of the IscA protein of Shigella flexneri, which forms a polar gradient at the old cell pole (54). Polar localization of IcsA is directed by a signal present in the protein, and it depends on OmpA and PhoN (55)(56)(57)(58)(59). It would be interesting to know if OmpA in this bacterium also forms a polar gradient that could direct the insertion of IcsA.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, we have previously shown that phoN2 , a gene located on a highly conserved region of the virulence plasmid of S. flexneri , encoding a periplasmic ATP-diphosphohydrolase (apyrase), participates, at least indirectly, to proper localization of IcsA at the bacterial surface [1] , [5] . By generating phoN2 ::HA fusions in the wild-type S. flexneri 5a strain M90T, we have shown that periplasmic PhoN2 strictly localizes at the bacterial poles, with a strong preference for the old pole, just beneath IcsA [1] . To evaluate whether PhoN2 and IcsA may interact for the correct exposition of IcsA, we conducted two-hybrid assays in yeast and cross-linking experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, a strong interaction of PhoN2 with the OM protein A (OmpA) was found. Sequence analysis indicated that OmpA binds PhoN2 through its periplasmic-exposed C-terminal domain (minimal interaction region, amino acid residues 166–250) [1] . OmpA is the major OM protein of Gram-negative bacteria principally involved in the structural integrity of the OM [6] .…”
Section: Introductionmentioning
confidence: 99%